Grenzen, Größenordnung und Intensitätsgefälle kommerziell-zentraler Einzugsgebiete - Meschede, Winfried (ERDKUNDE, 1971)
The main results of a survey, in the course of which the homes of 5,479 customers of 17 shops in Münster on the 3rd shopping Saturday before Christmas (12. 12. 1970) were pinpointed, indicated that: 1. The outer boundary of the market area of the central area shops corresponds to the outer limit of a theoretically determined pentangle, skewed to the NW. 2. Within the extra-urban market area of the central area shops the peripheral regions with low customer density can be separated from two centrally-situated, transversely lying regions of high density, whose axes run NS and EW in direction.3. In the inner-urban market area the actual customer density generally corresponds to the potential density. Because of this it is possible to define an intra-urban nuclear zone with high customer density in contrast to an inner-urban outer ring with lower customer density. The intra-urban nuclear zone of the market area of the central area foods shops shows - in an analogous fashion to the market areas of the shops of the outer urban area - a two-fold division into an interior nuclear zone, in which the accessibility of the shop by pedestrians is of great importance for the customer total, and an exterior nuclaer zone, in which the customer potential plays the most important role. 4. Variations in intensity of the market area of Münster change during the course of the day. In the second half of the day, not only the number of customers but also the average shop-customer dwelling distance showed a rise. The numbers of customers from outer areas - especially from medium distances - grew. The market areas of the retail shops changed more strongly than those of the department stores.